Impact Loading Rate Measuring with Different Heel Shoe Design for Transtibial Amputation - Abbas, Hamza (Al-Khwarizmi Engineering Journal, 2025)
Humans experience impact peaks due to the repetitive pressures placed beneath the heel during walking, and these peaks are marked by high rates and magnitudes of loading. Momentum is transferred from the ground to create impact peaks at the effective mass to the part of the body that stops moving at that point. The stiffness of the heel affects impacts generated by that momentum. This study aims to improve our understanding of how the body produces impact peaks and how the stiffness and features of the shoe heel affect parameters such as peak magnitude (Fmax) and impact loading rate (F’). A shoe heel model is presented, and walkers wearing less stiff foot heels are expected to have less effective mass and vertical impulse. A human amputee adult male participated in evaluating the model by walking in 15 different heel designs. Minitab software, which applies response surface approach, was used to acquire the shoe’s design properties. The subject walked on a force plate while 3D kinematic data were collected. Design of Experiment was carried out using Minitab software to determine the optimal shoe heel design (depending on material and shape) that reduces the impacting effect. Statistical results show that heel height has a more significant effect (p=0.053) on impact loading rate than elastic modulus and cross-sectional area. According to the optimisation results based on the response surface design, wearing a heel with a modulus of elasticity of 0.5864 mPa, an area of 60.0 cm2 and a height of 0.50 cm may help improve the amputee’s gait.